(untitled) (Veterinary Science, 2017)
The authors report a case of ectrodactyly in a 5-month-old German Shepherd. It is a description of the pathology aspects and the radiological characteristics of it. The limited information we have about this type of deformations contribute to disclose the different aspects of ectrodactyly while discussing the therapeutic management to adopt.